1089. Use of a Whole-Body Quantitative System Pharmacology Physiologically-Based Pharmacokinetic (QSP/PBPK) Model to Support Dose Selection of ADG20: an Extended Half-Life Monoclonal Antibody Being Developed for the Prevention of Coronavirus Disease (COVID-19). (4th December 2021) - Van Wart, Scott A; Tarbell, Evan D; Narayan, Kristin; Walker, Laura M; Connolly, Lynn E; Ambrose, Paul G
Abstract: Background: ADG20 is a fully human IgG1 monoclonal antibody engineered to have potent and broad neutralization against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and other SARS-like CoVs with pandemic potential as well as an extended-half-life. ADG20 is administered intramuscularly (IM). A QSP/PBPK model was constructed to support dose selection for a COVID-19 Phase 2/3 prevention trial (EVADE: NCT04859517). Methods: A QSP/PBPK model and a CDC reference adult body weight distribution (45–150 kg) were used to simulate 1000 concentration-time profiles for candidate single-dose regimens of ADG20 (150–450 mg IM). As serum virus neutralizing antibody (sVNA) titers are reportedly a key correlate of protection from COVID-19, a regression equation between time-matched serum ADG20 concentrations (following a 300 mg IM dose) and sVNA titers was developed using measured titers against authentic SARS-CoV-2 determined by a plaque reduction neutralization assay. Projected ADG20 serum concentrations relative to neutralization potency in vitro (90% inhibitory concentration [IC90 ]) for authentic SARS-CoV-2 were also evaluated. Results: The measured 50% neutralization titer (MN50; geometric mean [coefficient of variation, %]) was 1382 (32.7%) 13 days after a single 300 mg IM dose of ADG20. This was within the range of peak sVNA titers reported for COVID-19 vaccine recipients. Using the linear equation relating serum ADG20 concentration to time matched individual MN50 titers and the QSP/PBPK median PK prediction, the anticipated median MN50 exceeded the threshold for protection from SARS-CoV-2 infection established in a non-human primate adoptive transfer model for up to 52 weeks. Based on the QSP/PBPK median PK prediction, median ADG20 serum concentrations are projected to remain >100-fold above the ADG20 IC90 value of 0.011 mg/L against authentic SARS-CoV-2 for up to 52 weeks (Figure). Conclusion: Following administration of a single 300 mg IM dose, sVNA titers and concentrations of ADG20 are projected to remain above thresholds anticipated to be required for protection against COVID-19 for up to 52 weeks. These data support the evaluation of a single ADG20 300 mg IM dose for the prevention of COVID-19. Figure. QSP/PBPK model forecast of ADG20 300 mg IM in adults. Predicted median serum ADG20 concentration is shown with the dotted line representing 100× in vitro IC90 of 0.011 mg/L or 1.1 mg/L; the solid black line represents the simulated median; the shaded area represents the 90% prediction interval. The predicted median half-life of ADG20 300 mg IM exceeded 74 days. PBPK model inputs include Ln-normal Kd, FcRn of 9.55 nM (10% IIV); IM bioavailability of 100%; 15% IIV on muscle lymph RC; and Centers for Disease Control and Prevention weight distribution of 45–150 kg. FcRn, neonatal Fc receptor; IIV, inter-individual variability; Kd, dissociation constant; Ln, log-normal; RC, reflection coefficient. Disclosures: Scott A. Van Wart, PhD, Adagio Therapeutics, Inc. (Independent Contractor) Evan D. Tarbell, PhD, Adagio Therapeutics, Inc. (Independent Contractor) Kristin Narayan, PhD, Adagio Therapeutics, Inc. (Employee) Laura M. Walker, PhD, Adagio Therapeutics, Inc. (Other Financial or Material Support, Laura M. Walker is an inventor on a patent application submitted by Adagio Therapeutics, Inc., describing the engineered SARS-CoV-2 antibody.) Lynn E. Connolly, MD, PhD, Adagio Therapeutics, Inc. (Employee) Paul G. Ambrose, PharmD, Adagio Therapeutics, Inc. (Employee)